DFT calculations of tin dioxide crystals containing heavily-doped fluorine - Stashans, A. (2014)
First-principles calculations based on the density functional theory (DFT) within the generalized gradient approximation have been used in the present research. Fluorine doping in the SnO2 crystals has been carried out considering a number of different defect concentrations. Dopant influence upon structural, electronic and electrical properties of the tin dioxide has been discussed in detail. The system presents n-type electrical conductivity relating our work directly to a number of empirical studies in this area. An experimental fact that n-type conductivity tends to decrease at rather high fluorine impurity rates has been explained at the theoretical level. © 2014 World Scientific Publishing Company.